Tethered DNA scaffolds on optical sensor platforms for detection of hipO gene from Campylobacter jejuni - Gnanaprakasa, Tony J.; Oyarzabal, Omar A.; Olsen, Eric V.; Pedrosa, Valber A. [UNESP]; Simonian, Aleksandr L. (Elsevier, 2011)
DNA biosensors have gained increased attention over traditional diagnostic methods due to their fast and responsive operation and cost-effective design. The specificity of DNA biosensors relies on single-stranded oligonucleotide probes immobilized to a transduction platform. Here, we report the development of biosensors to detect the hippuricase gene (hipO) from Campylobacter jejuni using direct covalent coupling of thiol- and biotin-labeled single-stranded DNA (ssDNA) on both surface plasmon resonance (SPR) and diffraction optics technology (DOT, dotLab) transduction platforms. This is the first known report of the dotLab to detect targeted DNA. Application of 6-mercapto-1-hexanol as a spacer thiol for SPR gold surface created a self-assembled monolayer that removed unbound ssDNA and minimized non-specific detection. The detection limit of SPR sensors was shown to be 2.5 nM DNA while dotLab sensors demonstrated a slightly decreased detection limit of 5.0 nM (0.005 μM). It was possible to reuse the SPR sensor due to the negligible changes in sensor sensitivity (∼9.7 × 10 -7 ΔRU) and minimal damage to immobilized probes following use, whereas dotLab sensors could not be reused. Results indicated feasibility of optical biosensors for rapid and sensitive detection of the hipO gene of Campylobacter jejuni using specific ssDNA as a probe. © 2011 Elsevier B.V.
Keywords: Campylobacter jejuni; Diffraction optics technology; dotLab; hipO gene; Label-free DNA detection; Self-assembled monolayers; SPR; SPREETA; Diffraction optics; Label free; Bacteriophages; Biosensors; Diffraction; Electron energy levels; Genes; Oligonucleotides; Organic polymers; Probes; Scaffolds; Self assembled monolayers; Sensors; Surface plasmon resonance; DNA